154k views
2 votes
Which first step for solving the given system using substitution results in an equation without fractions? Solve for x in the first equation. Solve for y in the first equation. Solve for x in the second equation. Solve for y in the second equation.

User Nokla
by
5.6k points

2 Answers

3 votes

Answer:

b

Explanation:

edit:

the one after that is b

A= 1

B= 2

C= below

User Resorath
by
6.1k points
3 votes

Answer:

solve for x in the second equation is correct

Explanation:

Here is the complete question

Which first step for solving the given system using substitution results in an equation without fractions?

(2x+6y=7

(6x + 18y = 24.... 2

Solve for x in the first equation,

Solve for y in the first equation,

Solve for x in the second equation

The best equation to she will be equation 2 since all the coefficients are end numbers

Let us make x t subject f the formula from equation 2;

From 2: 6x+18y = 24

Subtract 18y from both sides

6x+18y-18y = 24-18y

6x = 24-18y

Divide through by 6

6x/6 = 24/6 - 18y/6

x = 4-3y.

You can see that the resulting expression of x is not a fraction. Hence solve for x in the second equation is correct

User Mark Khateeb
by
5.5k points